Protocol to implement and evaluate a culturally secure, strength-based, equine-assisted learning program, "Yawardani Jan-ga" (horses helping), to support the social and emotional wellbeing of Australian aboriginal children and young people. - Juli Coffin; Sharmila Vaz; Cheryl Kickett-Tucker; Helen Milroy; Craig Olsson; Meg Kirby; Lesley Nelson; Rob McPhee; Donna Cross (PLoS ONE)
Australian Aboriginal people experience stressors from inequalities across crucial social determinants, including deep and entrenched disadvantage and exclusion. The impact of unaddressed historical issues is pervasive and intergenerational. The disproportionate rates of Aboriginal youth suicide, juvenile detention and imprisonment highlight the inadequacy of existing social and emotional wellbeing programs and services for Aboriginal children and young people. There is increasing recognition in Australia that aligning social and emotional wellbeing interventions with Western values and conceptions of mental health is one of the main barriers to service uptake among Aboriginal people. This suggests fundamental questions remain unanswered about what type of services effectively address the complex constellation of social-emotional and wellbeing challenges arising from intergenerational poverty and trauma. Yawardani Jan-ga is an Aboriginal-led, operated, culturally secure, Equine-Assisted Learning (EAL) project designed by and with local Aboriginal young people, community Elders, members, and experts to address the complex constellation of social-emotional, spiritual and wellbeing needs of Aboriginal children and young people, aged 6-26 years, across multiple communities in the Kimberley region of Western Australia. EAL is a strengths-based learning approach where participants work with horses' inherent characteristics to learn transferable life skills, such as communication skills, self-awareness, and emotional regulation, to promote social and emotional growth and wellbeing. Although EAL has been previously used with Aboriginal children and young people internationally, they are yet to be widely used with Aboriginal people in Australia. Here, we describe the three subcomponents of the Yawardani Jan-ga implementation science project and the planned Participatory Action Research and phenomenological approaches to capture the distinctive experiences of participants and the local communities where the intervention is implemented. We anticipate that findings will build an evidence base that informs policy and practice by understanding key intervention elements of social and emotional wellbeing support for Aboriginal youth, how to incorporate Aboriginal worldviews across different stages of interventions, and how to capture impact best using culturally secure methods.